Draft Genome Sequence of the Nitrogen-Fixing Symbiotic Bacterium Bradyrhizobium elkanii 587 - Marcondes de Souza, Jackson Antonio [UNESP]; Tieppo, Eduardo; Magnani, Giovana de Souza; Carareto Alves, Lucia Maria [UNESP]; Cardoso, Rodrigo Luis; Cruz, Leonardo Magalhaes; de Oliveira, Lucas Ferrari; Raittz, Roberto Tadeu; de Souza, Emanuel Maltempi; Pedrosa, Fabio de Oliveira; de Macedo Lemos, Eliana Gertrudes [UNESP] (Amer Soc Microbiology, 2012)
The draft sequence of the genome of Bradyrhizobium elkanii 587 is presented. This was obtained using Illumina Next-Gen DNA sequencing combined with Sanger sequencing. Genes for the pathways involved in biological nitrogen fixation (the nif gene cluster), nod genes including nodABC, and genes for the type III protein secretion system (T3SS) are present.